2021
DOI: 10.1111/ecin.12978
|View full text |Cite
|
Sign up to set email alerts
|

Cultural relativity in consumers' rates of adoption of artificial intelligence

Abstract: Artificial intelligence (AI) is a cost-efficient innovation that challenges customers' consumption patterns and fears of uncertainty. This study assesses whether the likelihood that consumers adopt AI in banking services depends on tastes across different cultures. We propose a culturally-augmented Arrow-Bilir-Sorensen model to assess the propensity that consumers use AI. Analyses of a unique ING Bank dataset encompassing 11,000 respondents from 11 countries reveal that success rates for the diffusion of robo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 99 publications
(108 reference statements)
0
13
0
1
Order By: Relevance
“…The field of cultural theory has seen contributions from various influential individuals, including Arendt [49], Leidner and Kayworth [50] and Karl Marx, among others. Similarities exist in culture based on locations and markets, which, in turn, influence individuals' preferences [51].…”
Section: B Hofstede's Cultural Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The field of cultural theory has seen contributions from various influential individuals, including Arendt [49], Leidner and Kayworth [50] and Karl Marx, among others. Similarities exist in culture based on locations and markets, which, in turn, influence individuals' preferences [51].…”
Section: B Hofstede's Cultural Dimensionsmentioning
confidence: 99%
“…The cultural-based development (CBD) model combines psychological and cultural factors as well as uncertainty to understand innovation adoption [54,55]. The CBD model asserts that information plays a critical role in technology adoption and that culture significantly influences the exchange of information [51]. A recent study conducted in 11 countries found that the diffusion of roboadvisory financial services differs based on the cultural boundedness of choice in retail banking [51].…”
Section: B Hofstede's Cultural Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, domestic researchers paid more attention to the impact of cross-cultural adaptation. Specifically, Tubadji et al (2021) showed that the relationship between cultural intelligence, cultural novelty, and cross-cultural adaptation was the inverted U-shaped curve. Meanwhile, cross-cultural management practice and cultural adaptation had a significantly positive correlation, in which organizational support played a mediating role, while cross-cultural adaptation had a great impact on entrepreneurs' entrepreneurial intention and entrepreneurial performance.…”
Section: Related Workmentioning
confidence: 99%
“…CBD is a specific research paradigm that studies culture in economic choice and develops a unique methodology for its empirical and theoretical exploration (Tubadji 2012(Tubadji , 2013(Tubadji , 2020. The CBD Research paradigm has been employed in studying how culture matters in explaining human behaviour in relation to migration (Tubadji and Nijkamp 2015), school-to-work-transition (Tubadji et al 2017), productivity (Tubadji 2013), innovation (Tubadji et al 2021c(Tubadji et al , 2021d, inequality (Tubadji et al 2020a), and entrepreneurship (Tubadji et al 2019). Consequently, in CBD's terms, entrepreneurship is viewed as a function of the complex dynamics in the cultural context (Tubadji 2012(Tubadji , 2013(Tubadji , 2020, which links CBD very closely to the sociological theory of cultural capital (Bourdieu 1986).…”
Section: Introductionmentioning
confidence: 99%